The Effect of Cash Ratio, Debt to Equity Ratio, and Total Asset Turnover on Profit Growth with Firm Size as a Moderating Variable in Financial Sector Companies Listed on the Indonesia Stock Exchange (2022–2024) - Ridwansyah Ridwansyah; Heni Safitri; Dedi Hariyanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of Cash Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on Profit Growth, with Firm Size as a moderating variable in financial sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. The research employs a quantitative associative method using Moderated Regression Analysis (MRA). The results indicate that, simultaneously, CR, DER, and TATO have a significant effect on profit growth. Partially, DER and TATO show a positive effect, while CR has a negative effect. After being moderated by firm size, the correlation coefficient (R) increased to 0.994 with an R² value of 0.989, indicating that firm size strengthens the relationship between financial ratios and profit growth. These findings suggest that maintaining a balanced level of liquidity, an optimal capital structure, and efficient asset utilization is essential for improving profitability. Future research is recommended to include additional variables such as Return on Assets (ROA), Good Corporate Governance (GCG), or dividend policy to provide a broader understanding of the determinants of profit growth.